Timing of Occurrence Is the Most Important Characteristic of Spot Sign. Issue 5 (May 2016) - Wang, Binli; Yan, Shenqiang; Xu, Mengjun; Zhang, Sheng; Liu, Keqin; Hu, Haitao; Selim, Magdy; Lou, Min
Abstract : Background and Purpose—: Most previous studies have used single-phase computed tomographic angiography to detect the spot sign, a marker for hematoma expansion (HE) in spontaneous intracerebral hemorrhage. We investigated whether defining the spot sign based on timing on perfusion computed tomography (CTP) would improve its specificity for predicting HE. Methods—: We prospectively enrolled supratentorial spontaneous intracerebral hemorrhage patients who underwent CTP within 6 hours of onset. Logistic regression was performed to assess the risk factors for HE and poor outcome. Predictive performance of individual CTP spot sign characteristics were examined with receiver operating characteristic analysis. Results—: Sixty-two men and 21 women with spontaneous intracerebral hemorrhage were included in this analysis. Spot sign was detected in 46% (38/83) of patients. Receiver operating characteristic analysis indicated that the timing of spot sign occurrence on CTP had the greatest area under receiver operating characteristic curve for HE (0.794; 95% confidence interval, 0.630–0.958; P =0.007); the cutoff time was 23.13 seconds. On multivariable analysis, the presence of early-occurring spot sign (ie, spot sign before 23.13 seconds) was an independent predictor not only of HE (odds ratio=28.835; 95% confidence interval, 6.960–119.458; P <0.001), but also of mortality at 3 months (odds ratio =22.377; 95% confidence interval, 1.773–282.334; P =0.016). Moreover, the predictive performance showed that the redefined early-occurring spot sign maintained a higher specificity for HE compared with spot sign (91% versus 74%). Conclusions—: Redefining the spot sign based on timing of contrast leakage on CTP to determine early-occurring spot sign improves the specificity for predicting HE and 3-month mortality. The use of early-occurring spot sign could improve the selection of ICH patients for potential hemostatic therapy.